The use of Ground Granulated Blast Furnace Slag (GGBS) as Partial Cement Replacement in Brick - Hashim, Muhammad Syahir; Abdul Hamid, Noor Azlina (Recent Trends in Civil Engineering and Built Environment, 2023)
The production of Ordinary Portland Cement (OPC) has contributed to excessive emission of carbon dioxide to the atmosphere. The replacement of OPC with certain percentage of supplementary cementing material (SCM) can reduce the usage of OPC. Thus, the purpose of this study is to use Ground Granulated Blast Furnace Slag (GGBS) as partial cement replacement in sand cement brick. Since GGBS is a waste product, by using it as cement replacement significantly can reduce our environmental pollution. The experimental work was carried out to determine the physical and mechanical properties of sand cement brick containing high amount of GGBS as partial cement replacement and to obtain the optimum percentage of GGBS in brick. The percentage of GGBS for partial cement replacement are 30%, 40% and 50 %. A 215 mm x 103 mm x 65 mm (length x depth x height) size of brick is used to produce 48 samples of brick. The brick samples were tested after curing days of 7 and 28 days. The physical and mechanical test were carried out to achieve the objectives of the project such as density test, water absorption test, shape and size test and compressive test. From experimental results it can be concluded by using 30% of GGBS can increased the compressive strength of cement brick compared using fully OPC. The samples that use 40% and 50% of GGBS was lower than the strength that used 30% of GGBS. Therefore, 30% of GGBS replacement in cement brick was the optimum percentage and exceed the minimum requirement in standard of compressive strength cement bricks.